Tribological and machining characteristics of a minimum quantity lubrication (MQL) technology using GO/SiO2 hybrid nanoparticle water-based lubricants as cutting fluids - Lv, Tao; Huang, Shuiquan; Hu, Xiaodong; Ma, Yaliang; Xu, Xuefeng (International journal of advanced manufacturing technology, 2018)
Minimum quantity lubrication (MQL) technologies using vegetable oil lubricants as cutting fluids have attracted much attention as they have excellent machining performance and are environmentally friendly. Nevertheless, oil-based MQL tends to produce high cutting temperatures owning to the low cooling capability of oil lubricants. In this work, an MQL technology that utilizes graphene oxide/silicon dioxide (GO/SiO 2 ) hybrid nanoparticle water-based lubricants as cutting fluids was developed, and its tribological and machining characteristics were comparatively investigated using four-ball and milling testing units. The mass ratio of GO to SiO 2 was also varied to achieve optimal performance. The results showed that GO/SiO 2 water-based MQL reduced coefficient of friction (COF) and worn scar diameter (WSD) significantly, and improved machining performance compared with individual GO and SiO 2 water-based MQLs, as well as showed a comparative performance with traditional vegetable oil-based MQL. The superior performance of GO/SiO 2 water-based MQL was attributed to the fact that GO/SiO 2 hybrid nanoparticle additives entered the rubbing interface and formed a composite protecting film consisting of a self-lubrication layer of GO and a tribo-thin layer of SiO 2 , which prevented the interface from direct contact and smoothened asperities.